Crop Disease Detection in Image Processing Using MATLAB - P, Archana (International Journal of Psychosocial Rehabilitation, 2020)
The Crop disease detection system is to be observe the disease of the affected leaf of the crop using image processing, K-mean clustering is used to divide an image into the respective clusters and to extract a leaf’s colour and texture characteristics, following the pre-processing phase, which aims to remove image noises and poor resolution. Eventually, the parameters were fed into MATLAB to carry out the final classification.